PUBLIC SCHOOL TEACHER'S PERCEPTION ON FACTORS INFLUENCING TEACHING OF BIOLOGY IN SENIOR SCHOOL IN KWARA STATE - Gbigbadua Abdulraheem Dare(Ph.D); Olufunke Olayinka KAYODE (Ph.D) (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
This study investigates the perceptions of public school teachers with regards to factors that shape the teaching of biology in senior secondary schools in Kwara State, Nigeria. The effective teaching of biology holds a crucial position in equipping students with the requisite knowledge and skills necessary for careers in science and healthcare, underscoring the significance of comprehending the obstacles and enablers educators face in this domain. The study collects data through structured quantitative surveys using a quantitative approach. A simple randomly selected 50 seasoned biology teachers, drawn from public senior secondary schools situated in Kwara State, actively participated in the research. The study found that teaching biology plays a significant role for students pursuing careers in science and healthcare. While the current curriculum is effective in preparing the students for their chosen career, up-to-date resources are essential in enhancing the efficacy of biology instruction in public schools in Kwara State. There is also the need for adequate teacher training and professional development opportunities for effective biology teaching, coupled with the support of the school administration. Students need meaningful engagement and a keen interest in the biology teaching and learning process. There is a need to pay attention to the classroom facilities, laboratory apparatus, and equipment to facilitate effective teaching in biology. The study recommends the need for comprehensive and up-to-date curricula tailored towards biology education needs, continuous teacher training and professional development, support from the school administration to create an enabling environment for the teaching learning process, and student active engagement in classroom learning.